2018
DOI: 10.1038/s41598-018-32748-w
|View full text |Cite
|
Sign up to set email alerts
|

Bioprocessing strategies to enhance the challenging isolation of neuro-regenerative cells from olfactory mucosa

Abstract: Olfactory ensheathing cells (OECs) are a promising potential cell therapy to aid regeneration. However, there are significant challenges in isolating and characterizing them. In the current study, we have explored methods to enhance the recovery of cells expressing OEC marker p75NTR from rat mucosa. With the addition of a 24-hour differential adhesion step, the expression of p75NTR was significantly increased to 73 ± 5% and 46 ± 18% on PDL and laminin matrices respectively. Additionally, the introduction of ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Another difference between the rat and human OECs is that the human OECs do not appear to benefit from the presence of NT-3. Although the study was not carried out as part of this work, previous studies have shown that NT-3 significantly increased the expression of glial markers in rat cells [27]. For our human cell line, the presence of NT-3 seemed to increase the level of expression slightly, but not significantly.…”
Section: Human Oec Co-culture With Neuronsmentioning
confidence: 60%
See 4 more Smart Citations
“…Another difference between the rat and human OECs is that the human OECs do not appear to benefit from the presence of NT-3. Although the study was not carried out as part of this work, previous studies have shown that NT-3 significantly increased the expression of glial markers in rat cells [27]. For our human cell line, the presence of NT-3 seemed to increase the level of expression slightly, but not significantly.…”
Section: Human Oec Co-culture With Neuronsmentioning
confidence: 60%
“…Fibroblasts have a faster adhesion time than OECs. After 24 h, most fibroblasts will adhere to the tissue culture plastic, whereas OECs will still be in suspension [ 27 ]. After 24 h, the suspension was replated onto laminin-coated (20 μg/mL, Sigma-Aldrich, UK) wells.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations